Christopher Dyer. A Country Merchant, 1495-1520. Trading and Farming at the End of the Middle Ages. Oxford, Oxford University Press, 2012, 272 págs. - Casado Alonso, Hilario (Investigaciones de Historia Económica, 2019)
Sin resumen